2021
DOI: 10.1093/cdn/nzaa179
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-oxide (TMAO) Is not Associated with Cardiometabolic Phenotypes and Inflammatory Markers in Children and Adults

Abstract: Background Trimethylamine N-oxide (TMAO) is a diet- and microbiome-derived metabolite and a proposed biomarker of adverse cardiometabolic outcomes. TMAO studies have mainly been conducted in individuals with cardiometabolic disease, and studies in population-derived samples are limited. Objective We aimed to investigate the associations between plasma TMAO concentrations and its precursors [carnitine, choline, betaine, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…The key finding that plasma TMAO did not change after dietary choline intake is at odds with some former studies indicating positive associations with TMAO concentrations and adverse cardiovascular outcomes [ 11 , 35 , 38 , 39 , 40 , 41 , 42 ], although past findings are inconsistent [ 43 , 44 , 45 ]. However, this result is consistent with the previously recognized mechanistic role of TMAO in accelerated atherosclerosis [ 46 ] and hints that increased production of the gut microbiota-dependent PC metabolite, TMAO, rather than the presence of or exposure to its substrates (e.g., choline, carnitine, betaine, etc. ), is probably the overriding factor for the development of future cardiovascular events in humans.…”
Section: Discussionsupporting
confidence: 90%
“…The key finding that plasma TMAO did not change after dietary choline intake is at odds with some former studies indicating positive associations with TMAO concentrations and adverse cardiovascular outcomes [ 11 , 35 , 38 , 39 , 40 , 41 , 42 ], although past findings are inconsistent [ 43 , 44 , 45 ]. However, this result is consistent with the previously recognized mechanistic role of TMAO in accelerated atherosclerosis [ 46 ] and hints that increased production of the gut microbiota-dependent PC metabolite, TMAO, rather than the presence of or exposure to its substrates (e.g., choline, carnitine, betaine, etc. ), is probably the overriding factor for the development of future cardiovascular events in humans.…”
Section: Discussionsupporting
confidence: 90%
“…For example, TMAO was not associated with atherosclerosis measures in healthy early-middle-aged adults enrolled in the Coronary Artery Risk Development in Young Adults (CARDIA) study [ 34 ]. Furthermore, in a cohort of parents and children, TMAO was not related to metabolic syndrome nor markers of cardiovascular risk in either generation [ 35 ]. Thus, determining the relationships between TMAO and risk factors of CVD remain an important area of research prior to adopting dietary modifications to reduce TMAO concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In our study sample, there was no link between plasma TMAO and markers of inflammation, and plasma TMAO concentrations were lower than those linked to poor health outcomes in adults ( 29 ). Similarly, a study of healthy 11-y-old children in Australia found no association between TMAO and inflammatory biomarkers or indicators of metabolic syndrome ( 30 ). Given the unclear biological significance of plasma TMAO in young children, this finding does not warrant restriction of egg intake during the complementary feeding period.…”
Section: Discussionmentioning
confidence: 99%